MALACOLOGICAL DIFFERENCES BETWEEN THE OYSTERS CRASSOSTREA GRYPHOIDES (SCHLOTHEIM) AND CRASSOSTREA MADRASENSIS PRESTON - Durve, V S (Indian Journal of Fisheries, 2011)
The differences in malacological characters between Crassoslrea gryphoides (^&Aotheim)and C madrasensis Preston are tabulated. In many characters C. gryphoidesIs closer to C. verglaica Omelin